Association of gene polymorphisms of interleukin-10 (IL-10) with recurrent miscarriage (RM) after fertilization in vitro (IVF) - K. P. Golovatyuk (Kazimierz Wielki University, 2017)
The objective: to study genotype frequencies and allelic variants of gene IL-10-1082G>A (rs1800896), depending on the reproductive status and evaluation association with RM after IVF among the residents of Odessa region of Ukraine. Under supervision there were 240 patients of the main group with the RM after IVF and 100 apparently healthy fertile women in the control group K with a history of at least one term delivery and lack of spontaneous abortion episodes. SNPs typing of the genes for immune response in was used the polymerase chain reaction with the melting reaction products in the presence of "adjacent" oligonucleotides. It has been established that the carriers of AA genotype of the gene IL-10-1082G>A, which have been women-residents of Odessa region of Ukraine, had a high probability of occurrence of  RM during pregnancy after IVF (OR 2,56; 95% CI 1,51 - 4,35). Typing of SNPs of the immune response gene IL-10 (rs1800896) can be used as a method of early diagnosis and pregravid prediction of reproductive losses in women with RM after IVF.